A multisite genomic epidemiology study of Clostridioides difficile infections in the USA supports differential roles of healthcare versus community spread for two common strains. Issue 6 (28th June 2021) - Miles-Jay, Arianna; Young, Vincent B.; Pamer, Eric G.; Savidge, Tor C.; Kamboj, Mini; Garey, Kevin W.; Snitkin, Evan S.
Abstract : Clostridioides difficile is the leading cause of healthcare-associated infectious diarrhoea. However, it is increasingly appreciated that healthcare-associated infections derive from both community and healthcare environments, and that the primary sites of C. difficile transmission may be strain-dependent. We conducted a multisite genomic epidemiology study to assess differential genomic evidence of healthcare vs community spread for two of the most common C. difficile strains in the USA: sequence type (ST) 1 (associated with ribotype 027) and ST2 (associated with ribotype 014/020). We performed whole-genome sequencing and phylogenetic analyses on 382 ST1 and ST2 C. difficile isolates recovered from stool specimens collected during standard clinical care at 3 geographically distinct US medical centres between 2010 and 2017. ST1 and ST2 isolates both displayed some evidence of phylogenetic clustering by study site, but clustering was stronger and more apparent in ST1, consistent with our healthcare-based study more comprehensively sampling local transmission of ST1 compared to ST2 strains. Analyses of pairwise single-nucleotide variant (SNV) distance distributions were also consistent with more evidence of healthcare transmission of ST1 compared to ST2, with 44 % of ST1 isolates being within two SNVs of another isolate from the same geographical collection site compared to 5.5 % of ST2 isolates ( P -value=<0.001). Conversely, ST2 isolates were more likely to have close genetic neighbours across disparate geographical sites compared to ST1 isolates, further supporting non-healthcare routes of spread for ST2 and highlighting the potential for misattributing genomic similarity among ST2 isolates to recent healthcare transmission. Finally, we estimated a lower evolutionary rate for the ST2 lineage compared to the ST1 lineage using Bayesian timed phylogenomic analyses, and hypothesize that this may contribute to observed differences in geographical concordance among closely related isolates. Together, these findings suggest that ST1 and ST2, while both common causes of C. difficile infection in hospitals, show differential reliance on community and hospital spread. This conclusion supports the need for strain-specific criteria for interpreting genomic linkages and emphasizes the importance of considering differences in the epidemiology of circulating strains when devising interventions to reduce the burden of C. difficile infections.